The influence of organizational factors on information systems success in e-government agencies in Malaysia - Hussein, Ramlah; Abdul Karim, Nor Shariza; Mohamed, Norshidah; Ahlan, Abdul Rahman (City University of Hong Kong, 2007)
Information system success continues to be the subject of interest among IS researchers. The literature nevertheless offers limited understanding in regard organizational factors influencing IS success particularly in the public sector organizations. Using perceptual measures, this study aims to investigate the influence of organizational factors on IS success in selected public sector agencies in Malaysia. Survey questionnaires were gathered from 201 users from four central agencies located at the central administration complex in Putrajaya. The agencies are the Malaysian Administrative Modernization and Management Planning Unit (MAMPU), the Public Services Department (PSD), the Road Transport Department (RTD), and the Implementation Coordination Unit (ICU under the Prime Minister’s Department). The applications used by these agencies include the human resource management system (HRMIS), general office environment system (GOE), and project management systems (PMS). Based on related studies in the literature, six organizational factors and four IS success dimensions were used in designing the framework for this study. The framework is used to investigate the relationship between the identified organizational factors and IS success dimensions within the scope of the selected e-government agencies. The organizational factors are – top management support, decision-making structure, management style, managerial IT knowledge, goal alignment, and resources allocation, whereas the IS success dimensions include – systems quality, information quality, perceived usefulness, and user satisfaction. The study found that all the organizational factors are significantly and highly correlated to the four IS success dimensions under investigation. Further analyses reveal that goal alignment is the highest predictor of IS success, followed by management style and centralization of decision-making structure. Least expected was the top management support factor which appear to be the weakest predictor of IS success and its influence on IS success is insignificant. The study concludes that the findings are generally consistent with previous studies. On a specific note related to goal alignment, the public sector agencies can be seen experiencing similar impact to that of their private counterpart in terms of IS strategy alignment though they still generally subscribe to the traditional and centralized decision-making structure